Experiments for Isolating and Culturing Soil-borne Mycobacteria (Contemporary Publication) - Szelényi, Ferenc; Berencsi, György; Helmeczi, Balázs (Acta Agraria Debreceniensis, 2002)
On grounds of the several thousand tests performed in the field of this topic, the following conclusions may be arrived at:1. The informations available and the experimental data on soil mycobacteria are very incomplete.2. Of the 77 strains isolated from similar soil types so far, and adaptable for pure basic culture, 47 strains are confusingly similar, from morphological aspects, to the mycobacteria isolated from clinical material.3. The apparently homogeneous cultures isolated from the soil are generally co-infected and, therefore, the morphological, biochemical, and other physiological characteristics of the isolated strains can be studied only on base cultures after purification.4. For the isolation of the soil mycobacteria experiments qualified hitherto as most suitable processes the 4 or 1 per cent NaOH neutralized with H2SO4, and the 1 per cent NaOH or 1 per cent Na3PO4 treatments, on Gottsacker agar medium with plate or top pouring, at a temperature of 29 to 37 C°, in a soil suspension sequence of 1:500 to 1:5000 final dilution.5. The Ziehl-Nielsen staining of the isolated mycobacteria composed to sub-cultures is best performed by heating with an infra red radiator from above, instead of the gas flame used so far to heat from below.The repetition of the biochemical test of the hitherto isolated 77 purified strains is under progress, and will be reported on in our next scientific publication.